Butyrate Conditions Human Dendritic Cells to Prime Type 1 Regulatory T Cells via both Histone Deacetylase Inhibition and G Protein-Coupled Receptor 109A Signaling - Kaisar, Maria M. M.; Pelgrom, Leonard R.; van der Ham, Alwin J.; Yazdanbakhsh, Maria; Everts, Bart (Frontiers in Immunology, 2017)
Recently it has become clear that short chain fatty acids (SCFAs), and in particular butyrate, have anti-inflammatory properties. Murine studies have shown that butyrate can promote regulatory T cells (Tregs) via the induction of tolerogenic dendritic cells (DCs). However, the effects of SCFAs on human DCs and how they affect their capacity to prime and polarize T cell responses has not been addressed. Here we report that butyrate suppresses LPS-induced maturation and metabolic reprogramming of human monocyte-derived DCs (moDCs) and conditions them to polarize naive CD4+ T cells towards IL-10-producing type 1 regulatory T cells (Tr1). This effect was dependent on induction of the retinoic acid-producing enzyme retinaldehyde dehydrogenase 1 (RALDH1) in DCs. The induction of RALDH activity and Tr1 cell differentiation by butyrate was dependent on simultaneous inhibition of histone deacetylases (HDACs) and signaling through G protein-coupled receptor (GPR)109A. Taken together, we reveal that butyrate is a potent inducer of tolerogenic human DCs, thereby shedding new light on the cellular and molecular mechanisms through which SCFAs can exert their immunomodulatory effects in humans.